Evaluation of Ecosystem Services and Tradeoff and Synergy in the Alpine and Canyon Region of Southwest China Based on Multi-source Geographic Data - LIU Jing; XIANG Jiayi; ZHANG Donghai; LAN Mengyao; GUAN Yinghui (Shuitu Baochi Xuebao)
[Objective] The alpine and canyon region of Southwest China is a crucial ecological security barrier within the national “Three Zones and Four Belts” strategy, and it plays an essential role in ensuring national ecological security and promoting regional high-quality development. However, the ecosystem services and their trade-offs and synergies in this area remain unclear. [Methods] Three typical ecosystem services in the alpine and canyon region of southwest China from 2000 to 2020 were systematically evaluated using the InVEST model, RUSLE model, and WR index, in combination with multi-source geographic datasets. [Results] (1) From 2000 to 2020, carbon sequestration and water retention services in the alpine and canyon region of southwest China were steadily improved, with annual carbon sequestration increasing from 1 927 g/(m2·a) to 1985 g/(m2·a), and the WR index rising from 0.062 to 0.067. Spatially, carbon sequestration gradually increased from northwest to southeast, while water retention exhibited strong spatial heterogeneity. In contrast, soil retention services was overall deteriorated, decreasing from 263.50 t/(km2·a) to 226.25 t/(km2·a), with a reduction of 27.50% in the northwest Yunnan alpine canyon ecological maintenance zone. (2) The proportion of the area of ecosystem service hotspot areas increased by 5.41%, following a distribution pattern of the first-class hotspot areas > the non-hot spot areas > the second-class hotspot areas > the third-class hotspot areas form 2000 to 2020. (3) Carbon sequestration services exhibited a synergistic relationship with both water retention services and soil retention services, with synergy areas accounting for 54.91% and 44.46% of the total area, respectively. These synergies were mainly located in the southeastern Tibetan alpine canyon ecological maintenance zone and the eastern Tibetan-western Sichuan alpine canyon ecological maintenance and water retention zone. However, water retention and soil retention services displayed a trade-off relationship, with the synergy area accounting for only 20.14% of the total area. [Conclusion] The results can provide necessary references for scientifically formulating and implementing ecological protection policies and optimizing resource management strategies in the alpine and canyon region of Southwest China.